Neuromuscular performance of elite rugby union players and relationships with salivary hormones - Crewther, B. T.; Lowe, T.; Weatherby, R. P.; Gill, N.; Keogh, J. (The Journal of Strength and Conditioning Research, 2009)
This study compared the neuromuscular performance (speed, power, strength) of elite rugby union players, by position, and examined the relationship between player performance and salivary hormones, by squad and position. Thirty-four professional male rugby players were assessed for running speed (10-m, 20-m or 30-m sprints), concentric mean (MP) and peak power (PP) during a 70-kg squat jump (SJ) and 50-kg bench press throw (BT), and estimated 1 repetition maximum (1RM) strength for a box squat (BS) and bench press (BP). Tests were performed on separate days with absolute and normalized (power and strength only) values computed. Saliva was collected before each test and assayed for testosterone (Sal-T) and cortisol (Sal-C). In absolute terms, the backs demonstrated greater speed and BT MP, whereas the forwards produced greater SJ PP and MP and BS 1RM (p < 0.01). However, BT, SJ and BS performances were no different when normalized for body mass in kg0.67 (p > 0.05). A comparison (absolute and normalized) of BT PP showed no positional differences (p > 0.05), whereas BP 1RM was greater for the forwards (p < 0.05). These results may be attributed to genetic and/or training factors relating to the positional demands of rugby. The Sal-T and/or Sal-C concentrations of players correlated to speed, power, and strength, especially for the backs (p < 0.05), thereby confirming relationships between neuromuscular performance and hormone secretion patterns. Based on these findings, it was suggested that training to increase whole-body and muscle mass might facilitate general performance improvements. Training prescription might also benefit from acute and chronic hormone monitoring to identify those individuals likely to respond more to hormonal change.